Improvement of tribological properties of detonation carbosilicide coatings with subsequent pulsed-plasma treatment - Sagdoldina, Zh.B.; Rakhadilov, B.K.; Buitkenov, D.B.; Zhurerova, L.G.; Kenesbekov, A.B. (Karagandy University of the name of acad. E.A. Buketov, 2022)
This work considers the results of research of mechanical and tribological properties of surface layer of Ti3SiC2 coatings after exposure to pulsed-plasma energy flows. Varying of technological parameters of pulsed-plasma treatment is made by changing the distance of pulse exposure. The analysis of the obtained results shows that the pulsed-plasma treatment technology makes it possible to improve the properties of Ti-Si- C based coatings by strengthening the deposited compositions by modifying the structure with an increase in the number of МАХ-phases. It is established that the modification of the structural and phase state of the near-surface layers of the carbosilicide coatings leads to a change in their mechanical properties: an increase in the surface microhardness up to 1.8 times, a decrease in the dry friction coefficient by 1.5-2.0 times and an increase in wear resistance by 2.5 times. Based on the XRD analysis, it is established that the improvement of mechanical and tribological properties of Ti3SiC2 detonation coatings as a result of pulsed-plasma treatment is associated with phase transformations in the surface layer, in particular with an increase in the Ti3SiC2 phase content.
Импульстік–плазмалық өңдеумен детонациялық карбосилицидтік жабындардың трибологиялық қасиеттерін жақсарту
Повышение трибологических свойств детонационных карбосилицидных покрытий с последующей импульсно-плазменной обработкой
Keywords: detonation spraying; pulsed-plasma modification; microhardness; wear resistance; tribology; phase